Electronic Book of Network Security: Introduction to Network Security - Hoo, Cheong Yee (2003)
Technology is now widely used in a variety of educational support situations to improve the quality of education. It can be used to redress the imbalances of the old system and help in developing new teaching and learning strategies. The basis of this project is to design and develop an electronic book (E-book) tutorial to teach the basics of network security. E-books are developed with the intentions of overcoming the limitations of paper books. They have the advantages over paper books in that they are dynamic, reactive and able to provide the same features as well as new features such as hyper-linking, multimedia technology, digital annotating, digital book-marking and searching function. This project will pay particular attention to features and functionality of the e-book rather that the contents of the book. This project will involve the development of software application that will combine multimedia elements such as high-quality sound, text, photo images, two and three-dimensional graphics and animation into learning environment. The E-book will be created using Macromedia Authorware. In order to add interactivity and enhance the user interfaces to the e-book, Macromedia F1ash MX and Adobe Photoshop will be used. Finally, there will also be a quiz section for the user after they read the e-book.